Comparative analysis of the method of assignment by classes in GAVaPS - Lanzarini, Laura Cristina (2000)
Three alternatives within the method of assignment by classes are presented for the calculation of individuals lifetime in genetic algorithms with varying population size. (GAVaPS). In the proposed strategy (assignment by classes) individuals are grouped according to their fitness. The purpose is to use the allowed range of lifetime values in a way which is more suitable to search the optimum than proportional, linear and bilinear strategies. A comparative study of three possibilities of assignment by classes as related to the traditional methods is carried out, and results are shown over five functions. Finally, some conclusions are presented, along with possible future lines of work.